2004
DOI: 10.1089/10430340460732445
|View full text |Cite
|
Sign up to set email alerts
|

Acute Toxicity After High-Dose Systemic Injection of Helper-Dependent Adenoviral Vectors into Nonhuman Primates

Abstract: Systemic intravascular delivery of adenoviral (Ad) vectors for liver-directed gene therapy has been widely employed because of its simplicity, noninvasiveness, and potential for high transduction. For first-generation Ad vectors (FGAd), this results in high but transient levels of transgene expression and long-term hepatotoxicity due to viral gene expression from the vector backbone. Furthermore, high doses also result in an acute innate inflammatory response with potentially lethal consequences. Unlike FGAd, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
207
2
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 229 publications
(226 citation statements)
references
References 32 publications
16
207
2
1
Order By: Relevance
“…23 This interaction precipitates the acute phase of the innate immune response as animals treated with HD-Ad exhibit similar cytokine secretion patterns and toxicity profiles including coagulopathy and multiorgan failure as those described in animals treated with comparable doses of FG-Ad. 24,25 In addition, neutralizing antibodies against the viral capsid are produced, preventing successful readministration of HD-Ad vectors of the same serotype. 26 Thus, interaction of vector capsid proteins with the innate immune system is, at the moment, the final obstacle that must be overcome in the host with respect to the development of nonimmunogenic adenoviral vectors.…”
Section: Introductionmentioning
confidence: 99%
“…23 This interaction precipitates the acute phase of the innate immune response as animals treated with HD-Ad exhibit similar cytokine secretion patterns and toxicity profiles including coagulopathy and multiorgan failure as those described in animals treated with comparable doses of FG-Ad. 24,25 In addition, neutralizing antibodies against the viral capsid are produced, preventing successful readministration of HD-Ad vectors of the same serotype. 26 Thus, interaction of vector capsid proteins with the innate immune system is, at the moment, the final obstacle that must be overcome in the host with respect to the development of nonimmunogenic adenoviral vectors.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, dose-dependent acute inflammation was reported by Brunetti-Pierri and colleagues 76 in non-human primates following the administration of high-dose gutless vectors. However, innate response, as these recently reported, may be reduced by PEG modification, probably due to lower vector uptake by Kupffer cells in vivo.…”
Section: Gutless Adenovirus and Immune Responsementioning
confidence: 81%
“…56 Toxicity in non-human primates was assessed using different doses of gutless adenovirus and the results obtained showed that administration of high doses of adenovirus (10 13 viral particles/kg) induced a strong activation of the innate inflammatory response that caused the death of the animal. 76 In order to circumvent the decrease in transgene expression overtime, readministration with gutless vectors has been attempted in mice using different adenovirus serotypes. While readministration with different serotypes is possible using first-generation adenovirus, 55,56,[93][94][95] the level of transgene expression is lower after the second administration, probably due to crossreacting CTLs between the different serotype proteins.…”
Section: Gutless Adenovirus and Immune Responsementioning
confidence: 99%
“…There has been a discussion about the usefulness of this species for human clinical trials. 31 However, systemic administration of high-dose AdV in primates, clearly resulted in liver toxicity, 75 a result that could be predicted from studies in rodents and lagomorphs (Cichon et al 1 and above). It is also worth noting that the main AdV toxicity in humans was a consequence of an out-of-control immune reaction and high inflammation, 76 which was also found in baboons at the higher dose injected.…”
Section: Discussionmentioning
confidence: 96%
“…It is also worth noting that the main AdV toxicity in humans was a consequence of an out-of-control immune reaction and high inflammation, 76 which was also found in baboons at the higher dose injected. 75 In rodents and lagomorphs, cytokine levels were not investigated to our knowledge, but hematological modifications were evidenced. 1 Carefully and well-designed toxicology studies even in rodents, relying on sound biodistribution, can therefore help predicting vector's fate in humans, as in small molecules.…”
Section: Discussionmentioning
confidence: 99%